Performance Evaluation of Different RT-PCR Kits for the Direct Detection of SARS-CoV-2 in Preheated Specimens - Jain, Rajeev Kumar; Perumal, Nagaraj; Chaurasia, Deepti; Shrivastava, Rakesh; Ahirwar, Kamlesh Kumar; Sharma, Archa; Kapoor, Garima; Lalwani, Jaya (Journal of Laboratory Physicians, 2023)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has created high demand for molecular kits and consumables for mass screening of suspected individuals. Direct real-time polymerase chain reaction (RT-PCR) assay without nucleic acid extraction has several advantages in saving testing time and cost and helps in the rapid reporting of SARS-CoV-2. The present study evaluated the analytical performance of four SARS-CoV-2 RT-PCR for direct RT-PCR testing using preheated specimens.Methods A total of 100 clinical specimens were selected and divided into three different groups: (1) group I: 20 SARS-CoV-2 positive specimens with high viral load, viz., low Ct values (< 30 Ct), (2) group II: 50 SARS-CoV-2 positive specimens with low viral load, viz., high Ct values (> 30 Ct), and (3) group III: 30 SARS-CoV-2 negative specimens. Specimens were heat-inactivated at 70°C for 10 minutes and cooled down at 4°C and were evaluated for standard and direct RT-PCR method by using ViralDtect-II Multiplex Real-Time PCR kit, TaqPath COVID-19 Combo kit, COVIDsure Pro Multiplex RT-PCR kit, and Hi-PCR Coronavirus (COVID-19) Multiplex Probe PCR kit.Results Results showed that except ViralDtect-II kit, the other three TaqPath COVID-19 Combo kit, COVIDsure Pro kit, and Hi-PCR Coronavirus (COVID-19) RT-PCR kit were able to amplify all the SARS-CoV-2 genes in the direct RT-PCR method using preheated specimens. In group I specimens, 100% sensitivity was observed in all three RT-PCR kits. In group II specimens, COVIDsure Pro kit was found to be superior among other kits.Conclusion Direct RT-PCR method during pandemic situation is valuable and cost effective for the detection of SARS-CoV-2. All three TaqPath COVID-19 Combo kit, COVIDsure Pro kit, and Hi-PCR Coronavirus (COVID-19) RT-PCR kit can be used for direct RT-PCR method and COVIDsure Pro kit performance was found to be superior among all.
Keywords: COVID-19 disease; direct RT-PCR; preheated; RNA extraction; SARS CoV-2